Partial purification of the cyanide-resistant alternative oxidase of skunk cabbage (Symplocarpus foetidus) mitochondria. - Berthold, D A (1993)
A partial purification of the cyanide-resistant, alternative oxidase from skunk cabbage (Symplocarpus foetidus L.) spadix mitochondria is described. Skunk cabbage mitochondria were solubilized in N,N-bis-(3-D-glucon-amido-propyl)deoxycholamide and the alternative oxidase was purified using a batch DEAE-cellulose treatment, followed by precipitation with Extracti-Gel and chromatography on Sephadex G-200. Following pooling and concentrating of the most active fractions from the gel filtration column, a 20- to 30-fold purification of the alternative oxidase was obtained, with no evidence of contamination by cytochrome c oxidase (complex IV) or cytochrome c reductase (complex III). Polyacrylamide gel electrophoresis of the partially purified oxidase showed major polypeptides at 36 and 29 kD, both of which react with monoclonal antibodies raised against the Sauromatum guttatum alternative oxidase. The purified oxidase fraction showed no absorbance in the visible spectral region, and addition of sodium borohydride induced no absorbance changes in the ultraviolet region. The purified alternative oxidase catalyzed the four-electron reduction of oxygen to water in the absence of citrate, but catalyzed an apparent two-electron reduction of oxygen to hydrogen peroxide in the presence of 0.7 M citrate.